UPAYA PEMBINAAN AKHLAK PARA PELAJAR UNTUK MENGANTISIPASI DEGRADASI MORAL DI KALANGAN GENERASI MUDA - Akmir Akmir Akmir; Muh Ramadhan (Jurnal Ushuluddin Adab dan Dakwah, 2022)
Morals are a trait that is embedded in human beings, can be of good value or bad value. Morals are also not always synonymous with knowledge, words or deeds. People can know a lot about good and bad morals, but they don't necessarily have good morals themselves. People can speak soft and sweet words, but those words can come from the heart of a hypocrite. The Qur'an always emphasizes that the morals that a person commits, whether good or bad, will eventually reflect back on oneself. Whoever does good, that goodness will bounce back to himself. And whoever does reprehensible then the reproach will reflect on himself The era of globalization and information demands various efforts to develop and design educational policies by a nation, as well as special ones so that a society does not drown in the swift flow of globalization and information. Many unexpected changes have come from the two sides of the current world power which have a very large influence on people's lives, namely economic activities, developments in science and technology. On the other hand, such living conditions have also been able to penetrate the educational environment so that many students have deviated from religious teachings, such as being impolite at school, home, and society, they are even often involved in various acts of mass violence and behave in ways that tend to deviate. from religious teachings Therefore, moral education for students cannot be taken lightly. By fostering the morals of the students, it means that they have made a big contribution to preparing a better future for the nation, on the other hand, if students are allowed to fall into misguided actions, it means that they have allowed the nation and the country to fall into the abyss of destruction. By fostering the morals of students, the social environment is also getting better, safe, orderly and peaceful, which allows people to feel comfortable. Various environmental disturbances caused by the actions of some students will automatically disappear